Multifaceted Roles of ICP22/ORF63 Proteins in the Life Cycle of Human Herpesviruses - Wu, Ying; Yang, Qiqi; Wang, Mingshu; Chen, Shun; Jia, Renyong; Yang, Qiao; Zhu, Dekang; Liu, Mafeng; Zhao, Xinxin; Zhang, Shaqiu; Huang, Juan; Ou, Xumin; et al. (Frontiers in Microbiology, 2021)
Herpesviruses are extremely successful parasites that have evolved over millions of years to develop a variety of mechanisms to coexist with their hosts and to maintain host-to-host transmission and lifelong infection by regulating their life cycles. The life cycle of herpesviruses consists of two phases: lytic infection and latent infection. During lytic infection, active replication and the production of numerous progeny virions occurs. Subsequent suppression of the host immune response leads to a lifetime latent infection of the host. During latent infection, the viral genome remains in an inactive state in the host cell to avoid host immune surveillance, but the virus can be reactivated and reenter the lytic cycle.The balance between these two phases of the herpesvirus life cycle is controlled by broad interactions among numerous viral and cellular factors. ICP22/ORF63 proteins are among these factors and are involved in transcription, nuclear budding, latency establishment and reactivation. In this review, we summarized the various roles and complex mechanisms by which ICP22/ORF63 proteins regulate the life cycle of human herpesviruses and the complex relationships among host and viral factors. Elucidating the role and mechanism of ICP22/ORF63 in virus-host interactions will deepen our understanding of the viral life cycle. In addition, it will also help us to understand the pathogenesis of herpesvirus infections and provide new strategies for combating these infections.